Generalists versus specialists : iberian public firm performance in a gender perspective - Santos, Diogo Vicente Lopes da Silva (2022)
We propose that general managerial skills gathered during lifetime work experience are negatively related to firm performance even though generalist CEOs often demand a considerable pay premium. This negative performance should be alleviated with longer CEO tenure and vary with gender and macroeconomic conditions. We use CEO data of 88 public Iberian firms from 2010 through 2020 to build an index that represents general managerial skills over five categories that are transferable across industries and companies. Based on this sample, we find support for the negative association between the degree of general expertise and performance which is lessened in periods of crisis (in this case of the sovereign debt crises that affected both Portugal and Spain) and in case the CEO is a woman. Male CEOs with generalist skills, during crisis times, outperform their specialist counterparts, while the winners are generalist women who outperform specialist men in the top corporate position. These findings have repercussions for the more and more widespread practice of seeking to hire more generalist CEOs in an attempt to enhance firm performance, and the historical bias towards men leading the corporate world.